Effects of decompression on pain, range of motion and function in patients with acute vs chronic lumbar radiculopathy - Mariam Waseem; Syed Shakil Ur Rehman; Mehwish Ikram; Tooba Arif; Saimoon Rafi; Tayyaba Raza (Journal of the Pakistan Medical Association, 2022)
The purpose of this study was to determine the effects of manual lumbar decompression on pain, range of motion, and function in patients with acute vs chronic lumbar radiculopathy. Thirty patients fulfilling the eligibility criteria at Tehsil Headquarter Civil Hospital Daska were randomly placed into three groups: acute group (n=10), chronic group (n=10), and control group (n=10). Mean age of the participants was 33.3±8.5 years and the mean body mass index was 25.0±4.4. There were 12 males and 21 female participants. Group A and Group B were treated with decompression, lumbar mobilisation, hot packs, TENS and exercise therapy, while the patients in Group C were treated with lumbar mobilisation, hot packs and exercise therapy. ---continue